Microstructure and Mechanical Properties of 30CrMnSiA Parts Repaired by Laser Cladding - HU Shuzeng, CHENG Donghai, CHAO Bingxuan, YING Junlong, WANG De, WANG Jun, WANG Wenqin (Cailiao Baohu)
30CrMnSiA steel is extensively utilized in specialized tooling components， which frequently experience fatigue fractures and other damage mechanisms under cyclic stress during service.In this work，the laser cladding technology was adopted，and the microstructure and mechanical properties were analyzed based on process experiments.The optimal parameters were selected to perform laser repair on the damaged fork-shaped part of 30CrMnSiA， and its fatigue life was tested by a fatigue testing machine.Results showed that the microstructure within the repair layer was dense.The bonding interface between the repair layer and the base material was a typical metallurgical bonding，and no defects such as cracks occurred.The strength of the weld seam was higher than that of the base metal， and the tensile fracture was basically at the base metal.Besides，the specimen achieved a fatigue cycle count of 606 501，representing a 21.3%improvement in fatigue life compared to standard parts， meeting all operational requirements for specialized tooling components.